Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2135/cropsci2011.11.0584
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship Between Maize Resistance to Corn Borer Attack and Yield

Abstract: -Selection for reduced stalk tunnel length by the Mediterranean corn borer (MCB, 12 Sesamia nonagrioides Lef.), while maintaining yield under infestation, has already been evaluated. 13Significant reductions for tunnel length were reported, but yield showed a non significant 14 tendency to decrease with selection that could be due to increased inbreeding or significant 15 genetic correlation between yield and resistance. Simultaneously, the presence of major QTLs for 16 resistance in chromosome 4 has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Adverse effects on yield when applying phenotypic selection for increased resistance to stem tunneling by MCB corn borers agreed with results obtained in other breeding programs and give further support to the notion that trade-offs may exist between growth and yield versus defense against herbivores (Klenke et al, 1986;Butron et al, 2012Rosenthal andDirzo, 1997;Butron et al, 2012) regulator activated a defensive pathway and was sufficient to increase resistance to insects, but this activation conferred a cost in plant productivity. In the same way, Butron et al (2012) showed that breeding for increased when yield made plants more susceptible tois improved stem tunneling by MCBtunnel length increases (Butron et al, 2012).…”
Section: Annals Of Applied Biologysupporting
confidence: 79%
See 3 more Smart Citations
“…Adverse effects on yield when applying phenotypic selection for increased resistance to stem tunneling by MCB corn borers agreed with results obtained in other breeding programs and give further support to the notion that trade-offs may exist between growth and yield versus defense against herbivores (Klenke et al, 1986;Butron et al, 2012Rosenthal andDirzo, 1997;Butron et al, 2012) regulator activated a defensive pathway and was sufficient to increase resistance to insects, but this activation conferred a cost in plant productivity. In the same way, Butron et al (2012) showed that breeding for increased when yield made plants more susceptible tois improved stem tunneling by MCBtunnel length increases (Butron et al, 2012).…”
Section: Annals Of Applied Biologysupporting
confidence: 79%
“…Similarly, in previous studies, indirect effects on plant and ear heights have been observed when selection for increased resistance has been performed (Sandoya et al, 2010;Butron et al, 2012). In a previous study (Butron et al, 2012), Butron et al (2012) showed it has been even shown that markers potentially linked to plant height could have some effect on tunnel length under determined conditions.…”
Section: Annals Of Applied Biologymentioning
confidence: 59%
See 2 more Smart Citations
“…In general, tunnel length is better as selection criteria for increasing resistance to corn borers, but, in some genetic backgrounds, genetic linkage between yield and stalk tunneling by stem borers could make that selection for reduced tunnel length resulted in significant yield reductions (Schulz et al 1997;Kreps et al 1998;Butrón et al 2012). Pedigree selection for reduced tunnel length was successful for developing inbreds, such as EP105, that in hybrid combinations were comparable to hybrid checks for agronomic performance.…”
Section: Discussionmentioning
confidence: 99%